International relations in Southeast Asia the struggle for autonomy - Weatherbee, Donald E. (Lanham Rowman & Littlefield, 2014)
"Offers a clear and comprehensive introduction to the international relations of contemporary Southeast Asia. The author analyzes the Southeast Asian states' efforts to adapt to a regional international environment that is characterized by the security demands of the war on terrorism; the economic demands of globalism; and the political demands of nontraditional issues such as democracy, human rights, the environment, and gender. These shifting dynamics take place in a broader framework of diminished U.S. power and enhanced Chinese influence that could well undermine Southeast Asia's autonomy"-- Provided by publisher.
Introduction : the what and why of Southeast Asia -- The international actors in Southeast Asia -- The cold war in Southeast Asia -- ASEAN and regionalism in Southeast Asia -- Conflict and conflict resolution in Southeast Asia -- The South China Sea -- Transnational violence and crime in Southeast Asia -- Southeast Asia in the regional and international economies -- Human security in Southeast Asia's international relations -- Environmental issues in international relations in Southeast Asia -- Conclusion : nation-states, ASEAN, and autonomy.
Includes bibliographical references and index.
Keywords: ASEAN; Southeast Asia -- Foreign relations; Southeast Asia -- Politics and government -- 1945-.